2015
DOI: 10.7319/kogsis.2015.23.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Suitable Riparian Wildlife Passage Locations for Water Deer based on MaxEnt Model and Wildlife Crossing Analysis

Abstract: Stream restoration projects have become threats to riparian ecosystem in Rep. of korea. Riparian wildlife becomes isolated and the animals are often experience difficulties in crossing riparian corridors. The purposes of this study is to select suitable wildlife passages for wild animals crossing riparian corridors. Maximum entropy model and snow tracking data on embankment in winter seasons were used to develop species distribution models to select suitable wildlife passages for water deer. The analysis sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…The land around Sections I and II had lower percentages of Forested Areas than the land in Sections III, IV, and V, and higher percentages of Used Area and Grassland. This result is consistent with that of a previous study on the suitability of water deer habitats with MaxEnt, which suggested that water deer prefer Used Areas among the different land cover types [42]. The WVC Hotspots were characterized by higher percentages of open terrains such as Used Area, Grassland, and Barren Land.…”
Section: Wvc Hotspot Modellingsupporting
confidence: 92%
“…The land around Sections I and II had lower percentages of Forested Areas than the land in Sections III, IV, and V, and higher percentages of Used Area and Grassland. This result is consistent with that of a previous study on the suitability of water deer habitats with MaxEnt, which suggested that water deer prefer Used Areas among the different land cover types [42]. The WVC Hotspots were characterized by higher percentages of open terrains such as Used Area, Grassland, and Barren Land.…”
Section: Wvc Hotspot Modellingsupporting
confidence: 92%
“…특히 로지스틱회귀모형(Logistic Regression)은 연속형과 범주형 자료를 다 포함 시킬 수 있으며, 자료의 통계적인 가정이 덜 제 약적이고 출현/비출현 자료를 데이터를 이용할 수 있는 장점을 가지고 있다(Song, 2011). 또한 모형 내에서 다른 변수를 효과를 조절할 수 있 기 때문에 특정 변수의 실제적인 효과를 측정하 는데 유용하다(Song, 2011;Jeong, 2015). z )…”
unclassified